The Effect of Mathematics on Heritage Calculations Through Problem-Based Learning in MA Pondok Pesantren Al-Azhar Biibadillah Tahalak Kecamatan Batang Angkola - Masdelima Azizah Sormin; Mira Rahma Yanti Sormin (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2019)
This study aims to see the extent of the influence of mathematics in everyday life, one of which is the calculation of inheritance through problem-based learning. This research was conducted at the Al-Azhar Islamic Boarding School in Al-Azhar Islamic Boarding School in Tahalak, Batang Angkola District. This type of research is quasi-experimental research. The population in this study were all students of class XI MA Al-Azhar Islamic Boarding School in Biibadillah Tahalak Batang Angkola District. While the sample taken was class XI2 as many as 20 people as well as the experimental class and class XI1 as many as 20 people as well as the control class. Sampling is done through the pupose sampling technique. The research instrument used was a test of students' mathematical abilities in the calculation of inheritance. Statistical hypothesis testing in this study used the t test. Improving students' mathematical abilities in inheritance calculations that obtain problem-based learning is higher than students who use ordinary learning. The increase in students' mathematical abilities in the experimental class inheritance calculation was 71.6 with the highest score of 90 and the lowest value of 48 with a standard deviation of 10.57 while the ordinary learning class was 66 with the highest value of 80 and the lowest 54 and the standard deviation of 8.485. From the results of the posttest test, it can be seen the influence of mathematics on inheritance calculations through a problem-based learning model with the calculation of Fcount = 0.111 with a level of α = 0.05 and dk = 20 - 2 = 18 obtained by Ftable = 0.048. Thus obtained Fcount Ftable or 0.111 0.048, so Ha is accepted and Ho is rejected. To see the response of students from the results of student observations obtained tcount = 1.85 and at the level of α = 0.05 and dk = 20 + 20 - 2 = 38 obtained t table = 1.54. Thus it is obtained that tcount t table or 1.85 1.54, so Ho is rejected and Ha is accepted.